Makna Pembelajaran Berdiferensiasi di Sekolah Dasar Menurut Pandangan Aliran Filsafat Johann Heinrich Pestalozzi - RICHE AFRINA; LINORA LINORA; WIDIASTUTI WIDIASTUTI; ISMIRA ISMIRA; ALFROKI MARTHA (Indonesian Journal of Social Science Education (IJSSE), 2024)
This research aims to describe the meaning of differentiated learning in elementary schools according to the views of Johann Heinrich Pestalozzi's school of philosophy. In recent developments, the world of education and schools in Indonesia is increasingly discussing and good practices regarding differentiated learning. Therefore, it is necessary to have an alternative study regarding the views of educational philosophy figures regarding differentiated learning in elementary schools so that there are no misunderstandings regarding differentiated learning itself. The method used in this research is a literature study with technical content analysis. The meaning of differentiated learning in elementary schools. According to the view of Johann Heinrich Pestalozzi's philosophy, it is as follows: 1) Experience-based learning; 2) Learning Through the Senses, Pestalozzi suggests using the senses in learning. Pestalozzi believes that using the senses helps children to better understand concepts and relate them to the real world; 3) The Importance of Concrete Material; 4) Differentiation According to Ability and Speed; 5) Moral Education, Pestalozzi emphasized the importance of moral education in learning. Pestalozzi's view of differentiated learning views each child as a unique individual, with their own potential and needs. His thinking made an important contribution to the development of a more humanistic and personalized educational approach known as differentiated learning.